Endogenous Opioid Release in the Human Brain Reward System Induced by Acute Amphetamine Administration - Colasanti, Alessandro; Searle, Graham E.; Long, Christopher J.; Hill, Samuel P.; Reiley, Richard R.; Quelch, Darren; Erritzoe, David; Tziortzi, Andri C.; Reed, Laurence J.; Lingford-Hughes, Anne R.; Waldman, Adam D.; Schruers, Koen R.J.; et al. (Biological psychiatry (1969), 2012)
We aimed to demonstrate a pharmacologically stimulated endogenous opioid release in the living human brain by evaluating the effects of amphetamine administration on [11C]carfentanil binding with positron emission tomography (PET). Twelve healthy male volunteers underwent [11C]carfentanil PET before and 3 hours after a single oral dose of d-amphetamine (either a “high” dose, .5 mg/kg, or a sub-pharmacological “ultra-low” dose, 1.25 mg total dose or approximately .017 mg/kg). Reductions in [11C]carfentanil binding from baseline to post-amphetamine scans (ΔBPND) after the “high” and “ultra-low” amphetamine doses were assessed in 10 regions of interest. [11C]carfentanil binding was reduced after the “high” but not the “ultra-low” amphetamine dose in the frontal cortex, putamen, caudate, thalamus, anterior cingulate, and insula. Our findings indicate that oral amphetamine administration induces endogenous opioid release in different areas of human brain, including basal ganglia, frontal cortex areas, and thalamus. The combination of an amphetamine challenge and [11C]carfentanil PET is a practical and robust method to probe the opioid system in the living human brain.